Acute Exercise, Plasma Nitric Oxide, and Blood Pressure in Older Adults with Different Levels of Training Status: The Influence of Polymorphisms of Endothelial Nitric Oxide Synthase - Reia, Thaís Amanda [UNESP]; Silva, Roberta Fernanda Da [UNESP]; Jacomini, André Mouraõ [UNESP]; Moreno, Ana Maria Guilmo [UNESP]; Ferezin, Letícia Perticarra; Pereira, Sherliane Carla; Lacchini, Riccardo; Dionísio, Thiago José; Santos, Carlos Ferreira; Zago, Anderson Saranz [UNESP] (Human Kinetics, 2021)
Background: This study aimed to analyze the acute effect of physical exercise on nitric oxide concentration and blood pressure (BP) in older adults with different levels of training status (TS) and verified the influence of endothelial nitric oxide synthase polymorphisms on these variables. Methods: A total of 145 older adults were divided into good TS (G1) and weak TS (G2). Participants were subjected to a 40-minute treadmill walk (40%-60% of maximum oxygen consumption) with BP measurements and blood collections for plasma nitrite and oxidative stress biomarkers at pretest and posttest moments. Data were analyzed by 2-way repeated-measures with Sidak post hoc test (P < .05) and multivariate linear analysis. Results: After acute exercise, G2 showed an increase in oxidative stress biomarkers (P = .008), and both groups showed an increase in systolic BP (P < .001). Polymorphisms 894G > T and intron 4b/a had no association with nitrite and BP. However,-786T > C polymorphism showed an association with reduced systolic and diastolic BP (TT genotype) and increased diastolic BP (TC genotype). Higher TS level was also associated with lower BP. Conclusion: The maintenance of good TS levels may have a protective effect on cardiovascular risks regardless of the genetic profile.
Keywords: Aging; Cardiovascular health; Chronic disease; Treadmill walk